2018
DOI: 10.1016/j.scitotenv.2017.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus activators contribute to legacy phosphorus availability in agricultural soils: A review

Abstract: Phosphorus (P) is one of the most limiting macronutrients for crop productivity and P deficiency is a common phenomenon in agricultural soils worldwide. Despite long-term application of phosphate fertilizers to increase crop yields, P availability is often low, due to the high affinity of phosphate for the soil solid phase. It has been suggested that the accumulated (surplus) P in agricultural soils is sufficient to sustain crop yields worldwide for about 100years. In this paper, we try to clear up the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
242
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(305 citation statements)
references
References 151 publications
4
242
1
11
Order By: Relevance
“…Phosphorus deficiency is one of the greatest limitations in the development of agriculture and forestry ( Zhu et al., ). In this study, P deficiency significantly decreased the biomass dry weight, and shoot dry weight of F. mandshurica seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus deficiency is one of the greatest limitations in the development of agriculture and forestry ( Zhu et al., ). In this study, P deficiency significantly decreased the biomass dry weight, and shoot dry weight of F. mandshurica seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important for P, which occurs primarily as apatite (calcium phosphate) in young soils, and strongly complexed with iron and aluminium oxides or as secondary calcium phosphates in older or highly weathered soils (Walker & Syers, 1976). Roots and microbes, including mycorrhizal hyphae, LMWOAs (Griffiths et al, 1994;Rineau et al, 2008), which facilitate release of orthophosphate from phosphate minerals through complex and poorly understood mechanisms (Zhu et al, 2018). Although both EM and AM hyphae release LMWOAs (Plassard & Dell, 2010), Allen et al (1996) found oxalate crystals on only EM hyphae in southern California.…”
Section: New Phytologistmentioning
confidence: 99%
“…Soil P usually limits plant growth due to its poor mobility. Currently, overcoming P deficiency and increasing soil P availability is a necessary issue for achieving high crop productivity, highlighting the need to apply large amounts of inorganic P fertilizers in agricultural ecosystems [1][2][3][4]. Conversely, P has accumulated in agricultural soils due to the application of chemical fertilizers to mitigate the high P fixation capacity of acidic soils in Japan [2,5].…”
Section: Introductionmentioning
confidence: 99%